Recent developments in regulating “too big to fail” banks in the Philippines - Banderlipe, Mc Reynald S., II (Animo Repository, 2016)
This paper presents an overview of the recent developments in the financial regulation system that relates to the management of banks identified as “too big to fail” such that government response is needed to address the eventual failure of these institutions. First appeared in an announcement in the United States, the “too big to fail” clause is linked to the measures undertaken by the government to save large companies from apparent letdown, since their failure would result to economic fallout due to their interconnectedness with other entities for goods and services. The paper also provides an overview of the causes and implications of this clause such as the exposure of financial institutions to systemic risk and the moral hazard problem. In addition, the discourse sheds light on how global response takes action towards creating resolutions on these systemically important financial institutions, particularly in the Philippines, whose counterpart of “too big to fail” entities are identified as Domestic Systemically Important Banks (D-SIBs). Lastly, it presents alternative options that can contribute towards improving financial regulation without experiencing the trade-offs as a result of these actions. © 2016 by De La Salle University.